Analisis Rasio Solvabilitas (DAR, DER, TIE) Terhadap Kinerja Keuangan Perusahaan pada Sektor Keuangan (PT Adira Dinamika Multi Finance Tbk dan PT BFI Finance Indonesia Tbk Periode 2016-2020) - Selviya Rustiyana; Fenisi Resty; Yesi Gusteti (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2022)
Abstract: This study aims to find and analyze the effect of debt to asset ratio, debt to equity ratio and times interest earned on the financial performance of PT Adira Dinamika Multi Finance Tbk and PT BFI Finance Indonesia Tbk. This research was conducted through the official website of the Indonesia Stock Exchange (IDX) at www.idx.co.id. The data source used is secondary data in the form of financial statements for the 2016-2020 period. The data analysis technique used in this research is quantitative descriptive analysis technique, namely data in the form of numbers which include financial statements in the form of balance sheets and income statements that describe real circumstances or events in the company. The results of the study using the debt to asset ratio, debt to equity ratio and times interest earned shows that the financial condition of PT Adira Dinamika Multi Finance Tbk and PT BFI Finance Indonesia Tbk during the 2016-2020 period showed an unfavorable condition. This is evidenced by the company's inability to pay off debts to external parties and the analysis results do not meet the general industry average standards. Keywords: Financial Performance; Solvency Ratio; DAR; DER; TIE